Analisis Pengaruh Burnout, Job Insecurity Terhadap Turnover Intention Salesman - Septianna, Agatha (Catholic University Musi Charitas, 2021)
This research is to determinethe impact of of Burnout and Job Insecurity on turnover intention salesman within automotive industries in Palembang. This research using descriptive method. Data were collected by interview and distributing questionnaire for 100 respondents, salesman in automotive industries using convenience sampling. The statistical used in this research were multiple regression by using SPSS. Conclusion of this reseach shows that Burnout has significant negative impact on turnover intention, Job insecurity has significant positive impact on Turnover Intention. Furthermore Burnout and Job insecurity, simultaneously have significant positive impact on Turnover Intention. Keywords : burnout, job insecurity, turnover intention